Induction of mucosal immune responses and protection against enteric viruses: rotavirus infection of gnotobiotic pigs as a model - Yuan, Lijuan (Vet Immunol Immunopathol, 2002)
Enteric viruses are a major cause of diarrhea in animals and humans. Among them, rotaviruses are one of the most important causes of diarrhea in young animals and human infants. A lack of understanding of mechanisms to induce intestinal immunity and the correlates of protective immunity in neonates has impaired development of safe and effective vaccines against enteric viruses. Studies of candidate vaccines using an adult mouse model of subclinical enteric viral infections often do not predict vaccine efficacy against disease evaluated in neonatal large animals. A series of studies have been conducted using a neonatal gnotobiotic pig model of rotavirus infection and diarrhea to identify correlates of protective immunity and to evaluate traditional and novel vaccine approaches for the induction of mucosal immune responses and protection to enteric viruses. Gnotobiotic pigs recovered from infection with virulent Wa human rotavirus (HRV) (mimic natural infection) had high numbers of intestinal IgA rotavirus-specific primary antibody-secreting cells (ASCs) and memory B-cells (to recall antigen) measured by ELISPOT assay, which correlated with complete protection against rotavirus challenge. Most short-term IgA memory B-cells were resident in the ileum, the major site of rotavirus replication. Spleen, not the bone marrow, was the major resident site for longer-term IgG memory B-cells. Candidate rotavirus vaccines evaluated in pigs for their ability to induce intestinal or systemic ASC and protection against rotavirus infection and diarrhea included attenuated live virus, inactivated virus, and baculovirus-expressed double-layered rotavirus-like particles (2/6-VLPs). In combination with those candidate vaccines, various adjuvants, delivery systems, and immunization routes were tested, including incomplete Freund’s adjuvant for i.m. immunization, and a mutant Escherichia coli heat labile enterotoxin R192G (mLT) for i.n. immunization. It was shown that orally administered replicating vaccines were most effective for priming for intestinal IgA ASC and memory B-cell responses, but i.n. administered non-replicating 2/6-VLPs plus mLT were effective as booster vaccines. We conclude that protective immunity depends on the magnitude, location, viral protein-specificity, and isotype of the antibody responses induced by vaccination. Therefore highly effective enteric viral vaccines should: (i) induce sufficient levels of intestinal IgA antibodies; (ii) include viral antigens that induce neutralizing antibodies; and (iii) require the use of effective mucosal adjuvants or antigen delivery systems for non-replicating oral or i.n. vaccines.